Autonomous Foreign Policy and the Argentine Boycott of the U.S. forfeiture on Cuba - Piñero, María Teresa (Centro de Estudios Avanzados, 2017)
This project addresses the political ideas and events that, in the '70s in Argentina, gave rise to what Juan Carlos Puig called “heterodox autonomy”, a strategic position in the politics of foreign relations. Different actions took place in this period, from the open confrontation with the United States, regarding positions in international organisms, to the continuation of commercial agreements with this country, and the rapprochement with countries of the East and of the third world. In this context, it developed what would be referred to as the Argentinean boycott to the Cuban embargo, which, analyzed as a paradigmatic occurrence of heterodox autonomy, entailed a commercial strategy that, benefiting local, national and transnational companies, allowed its fruition.